`3/4 (3x+1) = 2(3-2x) +1`

The `3/4` needs to be distributed between the (3x+1) and the 2 needs to be distributed between the (3-2x):

`3/4 (3x) + 3/4(1)= 2(3) - 2 (2x) + 1`

`(9x)/4 + 3/4 = 6-4x +1`

`(9x)/4 + 3/4= 7-4x`

Eliminate the denominator by multiplying everything...

## View

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

`3/4 (3x+1) = 2(3-2x) +1`

The `3/4` needs to be distributed between the (3x+1) and the 2 needs to be distributed between the (3-2x):

`3/4 (3x) + 3/4(1)= 2(3) - 2 (2x) + 1`

`(9x)/4 + 3/4 = 6-4x +1`

`(9x)/4 + 3/4= 7-4x`

Eliminate the denominator by multiplying everything by the LCD(lowest common denominator) of 4:

`(9x)/4 times 4 + 3/4 times 4=7 times 4 - 4x times 4`

9x +3 = 28 - 16x

Notice the effect on the denominator

Now get your like terms together:

9x+16x = 28 -3

25x= 25

`x=25/25`

therefore **x=1**